RE-DESIGN SISTEM ANTRIAN UNTUK MENGOPTIMALKAN WAKTU ANTRIAN: STUDI KASUS JNE CABANG KOTA MAKASAR - Hendria, Richa; Sherlywati, Sherlywati (Jurnal Administrasi Bisnis, 2023)
This research is a case study on a shipping company in Indonesia. Queue service is one of the determinants of the success of the shipping company. This research is aimed at optimizing the waiting time of the queuing system at JNE Mataram City branch. The data used in this study is the result of direct observation of the object of research and interviews with the company. The model used in this research is the M/M/S Model (Multiple Channel Query System), and data processing using POM-QM software for Windows. The data used in this study are categorized into two categories, namely service data during peak and off-peak hours. The results showed that the service counter in the rush hour service category at JNE Mataram City Branch was not optimal because the standard target set by the company was still far from being achieved. The customer queue service target of six minutes is still far from the current practice of service time which takes an average of 15 minutes. The suggestion of this research is to redesign the service system of JNE counter service at the Mataram City branch by adding three counters to produce more optimal customer queue time.